Practical Implementation of Pair and Group Works as Communicative Learning Strategies to Increase Students’ HOTS in Speaking Skills: English - Karina Thohirah; Hanni Yukamana; Santi Mayasari (Journal of English Development, 2024)
Abstract Students are needed to learn to effectively speak in English, since it is one of the languages to communicate and intereact in most areas. But as it is foreign language, students may depend on direct instruction than being self-directed learners. Many students have yet to develop their higher-order thinking skills (HOTS), they struggle to think critically and relying more on memorization without a deep understanding especially when they need create produced skills. To handle the situation, this study aimed to increase students’ HOTS in speaking skills. This study was a Classroom Action Research (CAR) with three cycles within three meetings each cycle. There was a class called pre-intermediate that the researcher found most students have LOTS than HOTS. This study used Communicative Learning Strategies to increase students' HOTS in speaking skills by implementing Communicative Language Teaching (CLT) approach and asking them to work in groups and/or pairs. There were 18 participants with whom the researcher implemented the strategies. Data collection used were speaking assessment, observation, questionnaire, and documentation. The findings showed that CLS can increase students' HOTS. The speaking scores have reached the success criteria which are about 4.1 out of 5.0. The results of observation and questionnaires explained that class activities affected their thinking skills, and so did the documentation.